PENENTUAN CADANGAN PREMI DENGAN PERHITUNGAN PROSPEKTIF UNTUK ASURANSI PENDIDIKAN - HUTAPEA, ANGGIE EZRA JULIANDA; WIDANA, I NYOMAN; HARINI, LUH PUTU IDA (E-Jurnal Matematika, 2018)
The purpose of this research is to get formula to calculate premium reserve value with prospective calculation for education insurance. This study examines the value of premium reserves for people aged 40 years with a coverage period of 17 years. In determining the value of premium reserve using the prospective calculation. It will be started by completing the value of the Indonesian Mortality Table 2011 using the interest rate of 6.5%, calculating the cash value of the benefit, the annuity value, the net annual premium value, and the net monthly premium value. The results of this study indicate that the value of premium reserves with a prospective calculation for benefits paid at the end of the year and the premium reserve value for benefits paid at the time the insured dies, its value with the value of the cash price set by the insurer at the end of year- 17 on the insurance contract.